Performance of Electrocoagulation Process for Microplastic Fibre Removal from Laundry Wastewater - Marita Wulandari; Intan Dwi Wahyu Setyorini; Anggie Melinda Handayani; Ismi Khairunnissa Ariani; Ainun Zulfikar (Universitas Diponegoro, 2022)
Laundry wastewater contains not only detergent but also contains fabric fibres and threads. Microplastic fibres have been discovered as a potential source of microplastic fibres in synthetic clothing washed in the environment. To reduce microplastic concentration in wastewater, many approaches have been developed. Electrocoagulation is one of them. Using both synthetic microplastics and laundry wastewater samples, this study examined the performance of electrocoagulation methods to remove microplastics. The flocculation and deposition mechanisms remove microplastic fibre. This research was set up by using a reactor with a volume of 1 L, 60 V of voltage and 60 minutes of contact time. Electrical current of 5A and 10A was applied to remove microplastic fibres during electrocoagulation (EC). The removal efficiency of polyester fibre was 55-68 per cent for 60 minutes with a current of 5A and 42-85 per cent for 60 minutes with a current of 10A. Polyamide fibre removal efficiency in 60 minutes is 53 per cent to 74 per cent at 5A current and 57 per cent to 72 per cent at 10A current. According to this study, it can be concluded that EC can remove microplastic fibre from laundry effluent.